Ambiente visual para el aprendizaje de la trigonometria (2015)
The following article presents the degree project, called "Visual environment for the learning of trigonometry", where from an analysis of the materials used for the teaching of trigonometry, there were difficulties that affect students' comprehension. . Under the previous context, an interactive visual environment was designed and constructed that exposes the basic concepts of trigonometry, facilitating teaching in a ludic and dynamic way, which is reflected in a set of applications in Wolfram Mathematica.